Between children's discovery and pedagogical persuasiveness in narrative art. On pedagogically obvious and non-obvious film - Katarzyna Krasoń (Jagiellonian University Press, 2024)
The aim of this article is to show the importance of film in education. The goal of the considerations is to compare the educational offer, which often fails to meet the needs of children, and the entertainment films, whose message is decoded by the audience. Films included in the popular streaming offer and related to the Star Wars universe were presented as an example thereof.